Cachexia is a risk factor for negative clinical and functional outcomes in patients receiving chimeric antigen receptor T‐cell therapy for B‐cell non‐Hodgkin lymphoma. (9th February 2022) - Roy, Ishan; Smilnak, Gordon; Burkart, Madelyn; Hamilton, Elizabeth; Thorp, Katherine; Miyata, Sarah; Ma, Shuo; Pro, Barbara; Winter, Jane; Gordon, Leo; Karmali, Reem
Summary: Cachexia is a muscle‐wasting syndrome that is known to impact the clinical course of several cancer populations but has not been specifically investigated in patients receiving chimeric antigen receptor T (CAR‐T) cell therapy. In this study, we investigated the relationship between cachexia markers and several cancer and functional outcomes in a pilot population of aggressive B‐cell non‐Hodgkin lymphoma patients receiving CAR‐T. We found that the prognostic nutritional index was linked to progression‐free survival, overall survival, and disability‐free survival, while several additional weight and serum‐based markers of cachexia were also associated with negative outcomes. These data prompt further investigation of cachexia markers in populations receiving CAR‐T cell therapy.